Short-term and long-term effects of antimicrobial use on antimicrobial resistance in broiler and turkey farms. Issue 2 (4th March 2022) - Mughini-Gras, Lapo; Pasqualin, Dario; Tarakdjian, Jacopo; Santini, Andrea; Cunial, Giovanni; Tonellato, Francesca; Schiavon, Eliana; Martino, Guido Di
ABSTRACT: Antimicrobials have been widely used in poultry, promoting antimicrobial resistance (AMR) emergence and spread. Resistant bacteria selected by antimicrobial use (AMU) can contaminate the farm environment and transfer resistance genes to other bacteria, providing opportunities for persistence and (re-)colonization of subsequent flocks and potentially jeopardizing antimicrobial treatments. We investigated the effects of AMU on AMR in poultry in the long-term (due to historical AMU in the farm) and in the short-term (due to current AMU in a flock). Litter samples from 35 broiler and 35 turkey farms in North-East Italy were sampled longitudinally for AMR testing of E. coli indicator bacteria in 2019/2020. Differences in AMR as a function of historical AMU (Defined Daily Doses in 2016–2018), current AMU in the sampled flock, farm size and season were tested using Generalized Estimating Equation regression analysis. In both broilers and turkeys, the highest resistance levels were observed for sulfamethoxazole (>70%), followed by ampicillin (54–60%). Only a few positive associations between historical levels of penicillin use and the specific resistance levels to penicillin in broiler farms, and the overall historical AMU and resistance to trimethoprim in turkey flocks, were significant. Current AMU showed significant effects on resistance to sulfamethoxazole, trimethoprim, ciprofloxacin and tetracycline in turkey flocks. Significant effects of farm size on some AMR levels were also identified. We found a stronger association between current AMU and AMR compared to historical AMU and AMR. AMR persistence in the farm environment in the absence of direct AMU pressure needs to be further investigated. RESEARCH HIGHLIGHTS: Sulfamethoxazole and ampicillin resistance are the highest in E. coli isolates of both broilers and turkeys. Short-term effects of antibiotic use on resistance are seen more often than long-term effects. Historical penicillin use is associated with penicillin resistance in broilers. There is an association between historical use and resistance to trimethoprim in turkeys.